Penerapan Problem Based Learning Menggunakan Open Ended Question Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa: The Application of Problem-Based Learning Using Open-Ended Questions to Improve Students' Critical Thinking Skills - Yunika, Yunika; Nurdianti, Raden Roro Suci; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This research was conducted to determine the effect of implementing Problem-Based Learning (PBL) with Open-Ended Questions on improving the critical thinking skills of students in the economics subject at State Senior High School 1 Ciamis. The study was motivated by the students' low level of critical thinking skills. This research employed a quasi-experimental method with a Non-equivalent Pre-test Post-test Control Group Design. Data were collected using tests and interviews. The population for this study consisted of all 178 eleventh-grade Social Sciences (XI IPS) students at SMAN 1 Ciamis for the 2024/2025 academic year. The sample, selected through purposive sampling, comprised class XI IPS 3, with 35 students, as the control group, and class XI IPS 4, with 36 students, as the experimental group. The research findings indicate a difference in the improvement of critical thinking skills. The experimental group, which used Problem-Based Learning with Open-Ended Questions, achieved an average post-test score of 58.33, whereas the control group, which used a direct instruction model, obtained an average post-test score of 46.50. Furthermore, there was a significant difference in the improvement of critical thinking skills between the experimental and control groups, with a Sig. (2-tailed) value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted.